Ontologia ISE/GRI: Integração do Índice de Sustentabilidade Empresarial (ISE) e a Global Reporting Iniciative (GRI) - REIS, Tâmara Batista (2015)
Sustainable development is essential for the overall economic and environmental balance required of the organizations management, control and reporting of sustainability data. For this a diversity index was proposed, which has caused low interoperability between information systems and difficulties in the exchange of information and experiences among organizations that adopt different methodologies for the representation and manipulation of sustainability data. This work presents a domain ontology for the representation of a common knowledge base among one of the most widely used sustainability indexes in Brazil, ISE, and the G4 Guidelines of the Global Reporting Initiative - GRI. The development of the semantic structure between this index and the G4 Guidelines can provide the availability of fast and consistent information and can also be used as a knowledge base for developing systems aimed at sustainability. The concepts of ontology were assessed by GRI taxonomy, developed through standardization and structuring of data with XBRL technology. This favors the use of ontology Web and making it independent of computational methodologies and difficulties faced by stakeholders using heterogeneous software and hardware.